Students’ and teachers’ perceptions and experiences of using social media in learning foreign languages - Anh, Le Thanh Nguyet; Tinh, Bui Thanh; Canh, Nguyen Van (International Journal of Evaluation and Research in Education (IJERE), 2025)
The benefits of social media applications have emerged as an advancement in teaching and learning foreign languages. However, it falls short of studies investigating the perspectives and experiences of educators and learners about social media usage in Vietnamese tertiary education contexts in rural areas. Therefore, this study examined the perceptions and experiences of teachers and students regarding the application of social media in foreign language learning at a university in the Mekong Delta, Southern Vietnam. The study was conducted with the participation of 199 students and 20 teachers. This study employed a mixed-methods approach, collecting data from questionnaires, and an in-depth interview. The findings showed that most teachers and students had a positive attitude towards applying this mode to teaching and learning foreign languages. However, they indicated some problems when utilizing those methods. Additionally, they suggested some measures for blending direct teaching and learning with social media based on their experience. The research results provided more insights into this field in the literature, especially in local settings.